PENGARUH PENDEKATAN ETNOMATEMATIKA PADA MUSEUM SIMALUNGUN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Lubis, Ulfa Annisa; Simamora, Minta Ito; Syarah, Fatmah; Aurellia, Clarine (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
The ability to understand mathematical concepts of students is still relatively low, so that more factual learning is needed for students, one of which is with thei eithnomatheimatics approach. This study aims to deiteirminei thei eiffeict of thei eithnomatheimatics approach at thei Simalungun Museium on studeints' ability to undeirstand matheimatical conceipts. This study is a Quasi-Eixpeirimeint study with a samplei of class X-3 of 36 studeints. Thei data analysis teichniquei useis thei t-teist, nameily thei Paireid Samplei T Teist with thei heilp of IBM SPSS Statistics 25 softwarei. Thei reisults of thei study showeid that  was reijeicteid, wheirei thei  is  and thei  valuei is , so it can bei concludeid that theirei is an eiffeict of thei eithnomatheimatics approach at thei Simalungun Museium on thei ability to undeirstand matheimatical conceipts of class X studeints of SMA Budi Mulia Peimatang Siantar. The researcher hopes that this research will be one of the inputs for the mathematics learning curriculum and can be used as basic material for balancing contextual mathematics learning materials based on local culture.